Renewable Energy Arbitration - Quo Vadis? Implications of the Spanish Saga for International Investment Law - Balcerzak, Filip (Brill, 2023)
Based on analysis of 21 arbitral awards rendered in the "Spanish saga" cases, this book discusses the current challenges faced by international investment law in the renewable energy sector, addressing questions such as which facts led to the unprecedented number of investor-state arbitrations filed against Spain, whether arbitral awards rendered against Spain have an impact on future proceedings commenced against other states, and which legal grounds in international law serve, or may potentially serve, as the basis for investors' claims in the renewable energy sector. Filip Balcerzak offers critical insight into generally applicable lessons for the future-both for adjudicators of renewable energy disputes and for policy-makers.